2007
DOI: 10.1007/s10803-007-0493-y
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Development and Initial Testing of a Questionnaire Version of the Environmental Rating Scale (ERS) for Assessment of Residential Programs for Individuals with Autism

Abstract: There is a lack of validated autism-specific outcome measures for large-scale evaluation of the effectiveness of psycho-educational programmes. To fill this gap the Environment Rating Scale (ERS) was adapted from an interview version to a staff-completed questionnaire version (ERS-Q). The ERS-Q was tested regarding data quality, validity, reliability and ease of understanding amongst 18 residential staff members. The ERS-Q and ERS showed comparable reliability (alpha = 0.89 and 0.93, respectively) and their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Possible explanations for the observed problems with this item in the Developmental Assessment and Planning subscale may relate to cultural differences between Sweden and the US (where the original ERS was developed) and/or ambiguities in wording. However, no such indications were found in the pilot study of the ERS-Q (Hubel, Hagell, and Sivberg 2008). Similar arguments also hold for other observations of potential item level problems.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Possible explanations for the observed problems with this item in the Developmental Assessment and Planning subscale may relate to cultural differences between Sweden and the US (where the original ERS was developed) and/or ambiguities in wording. However, no such indications were found in the pilot study of the ERS-Q (Hubel, Hagell, and Sivberg 2008). Similar arguments also hold for other observations of potential item level problems.…”
Section: Discussionsupporting
confidence: 76%
“…These concerns are relevant for the ERS and ERS-Q as this and other studies (Van Bourgondien et al 1998) have shown that their reliabilities are similar but compromised (albeit considered 'acceptable'). Given the requirement for expert on-site assessments to administer the original ERS and the maintained validity of its version (Hubel, Hagell, and Sivberg 2008), there thus appears to be a good case for the ERS-Q in future ASD studies. That is, the ERS-Q should be able to allow for considerably larger sample sizes without unreasonable funding demands.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, “program” will refer to educational services operating in public schools for children and youth with ASD. The Individuals with Disabilities Education Improvement Act (IDEIA 2004 ) specifies that for children with disabilities between the ages of 3 and 22, public schools have to provide free and appropriate educational services in the least restrictive environment. The law provides a number of specific details about these requirements (e.g., each student must have an individualized education plan; transition program has to start at 16).…”
Section: Introductionmentioning
confidence: 99%
“…The authors have published evidence of reliability and construct validity, although only 52 adolescents and adults with autism participated in the study. In a revision of the ERS , Hubel, Hagell, and Sivberg ( 2008 ) developed a questionnaire version of the scale, the ERS-Q , which could be completed by program staff. They found high internal consistency and substantial concurrent validity between the two scales, although again the number of participants in the study was quite low (n = 18).…”
Section: Introductionmentioning
confidence: 99%
“…The split-half reliabilities were good as well (for SPHERE, α = 0.96; for somatic distress, α = 0.82; for psychological distress, α = 0.89; for depression/anxiety, α = 0.93; for somatic distress, α = 0.88; for fatigue, α = 0.85; for neurasthenia, α = 0.94; and for somatization, α = 0.94). The validities of the SPHERE were tested by using the item-total correlations (Hubel et al, 2008). The results indicated that the item-total correlations were acceptable for all the subscales of the SPHERE (all the values were higher than 0.20).…”
Section: Resultsmentioning
confidence: 99%